Clinical and radiographic outcomes of a trabecular titanium™ acetabular component in hip arthroplasty: results at minimum 5 years follow-up. Issue 1 (December 2015) - Perticarini, Loris; Zanon, Giacomo; Rossi, Stefano; Benazzo, Francesco
Abstract Background Aim of this prospective study was to evaluate mid-term clinical and radiographic outcomes in total hip arthroplasty using an acetabular cup made of an innovative biomaterial, Trabecular Titanium™, whose highly porous structure and mechanical properties have been designed to mimic those of the natural bone, thus promoting a more physiological load transfer and a more durable fixation. Methods Between September 2007 and November 2009, 134 total hip replacements and eight revisions were carried out using DELTA-TT primary cups (Lima Corporate, Villanova di San Daniele del Friuli, Italy) in 133 consecutive patients. Mean age was 57.5 ± 14.7 SD (18–92) years. Diagnosis was primarily hip osteoarthritis in 85 (63 %) cases, developmental dysplasia of the hip (DDH) in 24 (18 %) and hip avascular necrosis (AVN) in 10 (7 %). All the revision procedures were due to aseptic loosening of the original implant. Approval of the Institutional Review Board of the IRCCS Policlinico San Matteo in Pavia was obtained for this study. Results Mean follow-up was 72.7 ± 7.9 SD (60–86) months. Average Harris Hip Score (HHS) significantly increased from 44.2 ± 5.4 SD (35–52) preoperatively to 95.9 ± 3.5 SD (88–100) at the last follow-up. No major post-operative complications were observed. 99.3 % of the acetabular components were radiographically stable at the last follow-up, without any radiolucent lines, sclerotic areas or periprosthetic osteolysis. Kaplan-Meier survival rate was 99.3 % at 5 years (95 % confidence interval). Conclusions This first account on the mid-term clinical performance of the DELTA-TT cup shows primary and secondary stability, thus representing an optimal solution for patients with high demands or affected by severe hip conditions.